2020
DOI: 10.1155/2020/8853053
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Profile among Patients with Suspected Bloodstream Infections in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Introduction. The burden of bloodstream infections (BSIs) has been warranted in Ethiopia. Globally, the emergency and raised resistance rate of bacterial antimicrobial resistance is becoming a prominent problem, and it is difficult to treat patients having sepsis. In this review, we aimed to determine the pooled prevalence of bacterial isolates among presumptive patients with bloodstream infections in Ethiopia. Methods. A systematic search was performed from PubMed/MEDLINE, Scopus, HINARI, ScienceDirect, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The overall prevalence of culture-positive results in this study, 28.06%, was comparable with the study done in Mekelle, Ethiopia, 28%, 16 in Addis Ababa Ethiopia, 27.9%, 19 in Weldia, Ethiopia, 25.78%, 43 and Athens, Greece, 29%. 44 However, the current prevalence is lower than the study done in Addis Ababa, Ethiopia, 40.2%, 45 in Bahir Dar, Ethiopia, 39.2%, 17 and in Addis Ababa, Ethiopia, 32.8%.…”
Section: Discussionsupporting
confidence: 86%
“…The overall prevalence of culture-positive results in this study, 28.06%, was comparable with the study done in Mekelle, Ethiopia, 28%, 16 in Addis Ababa Ethiopia, 27.9%, 19 in Weldia, Ethiopia, 25.78%, 43 and Athens, Greece, 29%. 44 However, the current prevalence is lower than the study done in Addis Ababa, Ethiopia, 40.2%, 45 in Bahir Dar, Ethiopia, 39.2%, 17 and in Addis Ababa, Ethiopia, 32.8%.…”
Section: Discussionsupporting
confidence: 86%
“…A high percentage of ESBL + AmpC-BL bacteria (67.1%) were identified meanwhile carbapenemase + MBL was found to be 30.7%. In this study, the rate of BSI was 28.1% which is comparable to other related studies conducted in Ethiopia with prevalence rates of 28.0% [ 39 ], 27.9% [ 40 ], and 25.8% [ 41 ]. However, the current result was higher than rates reported elsewhere18.2% [ 42 ], 15.8% [ 43 ], and lower than other studies conducted in Ethiopia which were 32.8% [ 19 ], and 39.2% [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…In Ethiopia, systemic review done in bloodstream infections showed that the proportion of blood stream infections ranged from (12.84–18.15%). The common pathogens isolated from bacterial infected patients were S. aureus and E. coli [ 17 ]. However, it is difficult to generalize these findings to all levels of health care facilities in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%